Molecularly imprinted polymer based electrochemical biosensors: overcoming the challenges of detecting vital biomarkers and speeding up diagnosis (2020)
Electrochemical biosensors for the detection of vital biomarkers is a well-established technology that utilises a transducer and recognition element in tandem to determine the presence of an analyte. There is growing interest in using Molecularly Imprinted Polymers (MIPs) as recognition elements in a wide range of sensing devices due to their economic viability and scalability. The inherent properties of polymer platforms, alongside the vast array of monomeric options, synthetic routes and incorporation strategies allow for the production of a multitude of sensitive and selective recognition elements that have significant advantages over classically utilised biological entities. MIPs exhibit superior chemical and thermal stability offering a wider variety of immobilization/incorporation strategies, virtually unlimited ambient shelf-life and a longer product lifetime, whilst the vast array of monomers available offer flexibility to their synthesis. Even though some sensor platforms have been reported for the detection of vital biomarkers, the use of MIPs has a number of challenges and drawbacks that need to be overcome in order to produce sensing platforms with the required sensitivity and specificity for clinical use. In this review, we will provide an overview of the reasoning behind using MIPs as recognition elements in electrochemical biosensors for vital biomarkers, discuss the problems synergizing MIPs and electrochemical read-out strategies and offer insights into the future perspectives of this promising and innovative technology.